(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
A new, simple, precise, accurate and reproducible RP-HPLC method for simultaneous estimation of Amitriptyline and Perphenazine in bulk and pharmaceutical formulations was developed. Separation of Amitriptyline and Perphenazine was successfully achieved on Inertsil ODS (250x4.6mm) 5µm column in an isocratic mode utilizing Methanol: ACN: Water (50:30:20) at a flow rate of 1.0 ml/min and eluents were monitored at 253nm with a retention time of 2.440 and 5.503 minutes for Amitriptyline and Perphenazine respectively. The method was validated and it was found to be linear. The values of the correlation coefficient were found to 0.992 for Amitriptyline and 0.9992 for Perphenazine respectively. The LOD for Perphenazine and Amitriptyline were found to be and 33.8µg/ml and 4.2 µg/ml. The LOQ for Perphenazine and Amitriptyline were found to be 20.88µg/ml and 12.12µg/ml respectively. The percentage recoveries for Amitriptyline and Perphenazine were found to be within the limit indicates that the proposed method is highly accurate. The method was extensively validated according to ICH guidelines.